2021
DOI: 10.1088/1742-6596/1869/1/012050
|View full text |Cite
|
Sign up to set email alerts
|

The effect of brewing time on pH values, polyphenols content, and antioxidant activities of coffee husk tea (cascara tea)

Abstract: Coffee husk tea, well-known as cascara tea, is a by-product of coffee processing. It contains phenol compound that has antioxidant activity. Total phenol compound is extracted by brewing process. It is commonly called polyphenol compounds. Polyphenols extraction process is deeply connected to brewing method, especially the time. The purpose of this study was to determine the effect of brewing time on pH, polyphenols content, and antioxidants activity of cascara tea. This study was carried out in Completely Ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
1
5
0
1
Order By: Relevance
“…Furthermore, the extract prepared with hot water from the coffee cherry husk dried in the sun has a DPPH free radical scavenging capacity of 50–78% . Additionally, DPPH radical scavenging activity ranged from 61.1 to 87.3% in coffee husk brewed at various brewing times . The variation could be attributed to differences in coffee cherry types, solvent types, climatic conditions, extraction methods, treatment conditions, and processing methods, which resulted in significantly different phenolic and flavonoid component concentrations, resulting in differences in DPPH free radical scavenging ability. , In this study, untreated coffee cherry husk extract was used as a control; its antioxidant activity (63.46 ± 0.11%) was lower than that of roasted coffee cherry husk at 150, 180 °C (10–20 min), and 200 °C (10 min).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the extract prepared with hot water from the coffee cherry husk dried in the sun has a DPPH free radical scavenging capacity of 50–78% . Additionally, DPPH radical scavenging activity ranged from 61.1 to 87.3% in coffee husk brewed at various brewing times . The variation could be attributed to differences in coffee cherry types, solvent types, climatic conditions, extraction methods, treatment conditions, and processing methods, which resulted in significantly different phenolic and flavonoid component concentrations, resulting in differences in DPPH free radical scavenging ability. , In this study, untreated coffee cherry husk extract was used as a control; its antioxidant activity (63.46 ± 0.11%) was lower than that of roasted coffee cherry husk at 150, 180 °C (10–20 min), and 200 °C (10 min).…”
Section: Resultsmentioning
confidence: 99%
“…Maharani et al ( 2021) [39] found that different leaching times affect the pH value of cascara extract.…”
Section: Phmentioning
confidence: 99%
“…Silverskin reached significantly higher TAC values (1S 58.17% and 2S 46.65%) than cascara (1C 36.54% and 2C 41.12%). Maharani et al [39] reported the TAC value of cascara in the range of 61.01-87.30%, depending on the time and method of extraction. These results differ from our findings.…”
Section: Total Antioxidant Capacity (Tac) and Total Polyphenols Conte...mentioning
confidence: 99%
“…The coffee processing industry generates a substantial volume of waste and by-products, primarily husks, accounting for approximately 45-50% of the total coffee harvest [ 1 ]. Vietnam is the second-largest coffee producer and exporter globally, with a cultivation area of over 695,000 hectares and an annual production of 1.76 million tons [ 2 ], accompanied by 800,000 tons of coffee husks annually.…”
Section: Introductionmentioning
confidence: 99%
“…Vietnam is the second-largest coffee producer and exporter globally, with a cultivation area of over 695,000 hectares and an annual production of 1.76 million tons [ 2 ], accompanied by 800,000 tons of coffee husks annually. Lacking efficacy in agriculture waste management might negatively affect the ecosystem [ 1 ].…”
Section: Introductionmentioning
confidence: 99%